2019
DOI: 10.1177/0883073819863992
|View full text |Cite
|
Sign up to set email alerts
|

Further Delineation of Pyridoxine-Responsive Pyridoxine Phosphate Oxidase Deficiency Epilepsy: Report of a New Case and Review of the Literature With Genotype-Phenotype Correlation

Abstract: In recent years, the clinical spectrum of pyridoxine phosphate oxidase (PNPO) deficiency has broadened. There are a growing number of patients with a transient or lasting response to pyridoxine in addition to cases that respond more traditionally to pyridoxal-phosphate. However, among pyridoxine-responsive patients with PNPO gene mutation, there are only a few reports on electroencephalogram (EEG) ictal/interictal patterns, and data regarding the outcomes are inconsistent. We describe a case of neonatal onset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…There were no specific imaging features identified in the brains of the reviewed patients. Different radiological findings were described; however, 34 patients (61.8%) had normal brain imaging 7‐9,11‐13,16,21,26‐33 . Di Salvo et al reported three patients with a c.347G > A (p. Arg116Gln) mutation in the PNPO gene who had normal brain imaging.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no specific imaging features identified in the brains of the reviewed patients. Different radiological findings were described; however, 34 patients (61.8%) had normal brain imaging 7‐9,11‐13,16,21,26‐33 . Di Salvo et al reported three patients with a c.347G > A (p. Arg116Gln) mutation in the PNPO gene who had normal brain imaging.…”
Section: Resultsmentioning
confidence: 99%
“…had normal brain imaging. [7][8][9][11][12][13]16,21,[26][27][28][29][30][31][32][33] The most common abnormality revealed on brain imaging was diffuse atrophy, which was observed in eight patients (14.5%), 8,9,16,20 followed by ischemic changes and encephalomalacia in five patients (5.5%), 1,13,16,17 and delayed myelination and atrophy in another three patients. 18,34,35 An additional two patients (2.5%) had diffuse or focal edema.…”
Section: Brain Imagingmentioning
confidence: 99%
“…Developmental delay is one common symptom manifested by PNPO-deficient patients ( 3 , 17 , 19 , 53 ), raising the question of whether specific developmental impairments lead to seizures. By providing flies with PLP during either the larval or adult stages, we have demonstrated that developmental impairments and seizures in adults are dissociable ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Developmental delay is one common symptom manifested by PNPO deficient patients [3,18,20,53], raising the ques- tion of whether specific developmental impairments lead to seizures. By providing flies with PLP during either the developmental or adult stage, we demonstrate that developmental impairments and seizures in adults are dissociable (Fig.…”
Section: Discussionmentioning
confidence: 99%